Pembuatan dan Uji Kualitas Sabun Transparan dengan Variasi Minyak Kelapa Murni atau Virgin Coconut Oil (VCO) Dan Minyak Kelapa Sawit - agus salim afrozi; Nurlisa Safitri; Siti Nurhasanah (Jurnal Ilmiah Teknik Kimia, 2021)
This research was conducted to make transparent soap appropriate to the Indonesian national standard (SNI 3235-2016). Transparent soap is made using raw materials of virgin coconut oil (VCO) and palm oil with NaOH, stearic acid. Addition of dyes and fragrances to increase the aesthetic value of the soap appearance. The addition of alcohol, sugar, and glycerin is used to bring out a clear and translucent color. The method of making transparent soap is a saponification method with a temperature used of 600C - 700C. The tests carried out include oil testing and transparent soap testing. Oil testing, among others: free fatty acids and density. Meanwhile, transparent soap testing, among others: pH, free fatty acids or free alkalis, moisture content, organoleptic, and preference test. Based on the results of tests that have been carried out by soap, it is known that the best formula for making transparent soap with palm oil is in the 1C20 formula where 150 mL of palm oil are used, 20 grams of sugar are dissolved in 10 mL of aquadest. Meanwhile, the best formula for making transparent soap from virgin coconut oil (VCO) is the 1Y20 formula where 100 mL of virgin coconut oil (VCO) are used, and 20 grams of sugar are dissolved in 10 mL of aquadest. Soaps that meet the standards of SNI 3532-2016 and SNI 06 - 3532 1994 are 1Y10,1Y20,1Y30 and 1Z10 soap.